Mixed Jacobi-like forms of several variables - Min Ho Lee (International Journal of Mathematics and Mathematical Sciences)
We study mixed Jacobi-like forms of several variables associated to equivariant maps of the Poincaré upper half-plane in connection with usual Jacobi-like forms, Hilbert modular forms, and mixed automorphic forms. We also construct a lifting of a mixed automorphic form to such a mixed Jacobi-like form.